Multimedia technologies as an educational environment in the formation of sociocultural competence - Albina F. Mukhamadiarova, Alina E. Rakhimova, (Opción, 2020)
This article is dedicated to the features and importance of using multimedia technologies in education and their role in the formation of sociocultural competence via comparative qualitative research methods. As a result, computer technologies increase the efficiency of education, they help to increase student motivation, reveal the potential for learning foreign languages and ultimately contribute to the formation of sociocultural competence. In conclusion, the use of computer technologies in the process of teaching foreign languages, is an indispensable resource for the formation of sociocultural competence.